2015
DOI: 10.1016/j.jesf.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of high- and low-intensity exercise bouts on leukocyte counts

Abstract: When the same participants were submitted to different exercise intensities, the acute and short-term effects of exercise on white blood cells were intensity-dependent immediately after exercise (i.e., lymphocytosis and monocytosis) and 2 hours after passive recovery (i.e., neutrophilia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 34 publications
9
49
0
2
Order By: Relevance
“…For example, Abdossaleh et al [6] reported that high-intensity exercise increased the total leucocyte, lymphocyte, monocyte, and neutrophil counts in college judoists. These findings are further supported by a more recent study in which a greater increase in the leucocyte count after high-intensity exercise in physically healthy and active young males compared to low-intensity exercise and no exercise [7]. McCarthy and Dale [8] also reported that leucocytosis is approximately proportionate to the intensity and duration of the exercise performed.…”
Section: Introductionsupporting
confidence: 66%
“…For example, Abdossaleh et al [6] reported that high-intensity exercise increased the total leucocyte, lymphocyte, monocyte, and neutrophil counts in college judoists. These findings are further supported by a more recent study in which a greater increase in the leucocyte count after high-intensity exercise in physically healthy and active young males compared to low-intensity exercise and no exercise [7]. McCarthy and Dale [8] also reported that leucocytosis is approximately proportionate to the intensity and duration of the exercise performed.…”
Section: Introductionsupporting
confidence: 66%
“…In blood, immediately after exhausting exercise, there is leukocytosis, as reported both in humans (Suchánek et al, 2010) and rodents (Krüger et al, 2008). This increase in blood leukocytes comprises higher counts of monocytes, granulocytes and the main subsets of lymphocytes, i.e., B and T (Th and Tc) cells (Dimitrov et al, 2010;Neves et al, 2015). Lymphocytosis is due to the higher release of catecholamines (Graff et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…; Neves et al . ) and these responses are dependent upon the intensity and duration of exercise (Malm et al . ; Kawanishi et al .…”
Section: Introductionmentioning
confidence: 99%